2007
DOI: 10.1111/j.1728-4465.2007.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Increased Lifetime Risk of Sexually Transmitted Infection Among Women in Ukraine

Abstract: Population-based, cross-sectional data from 3587 ever-married Ukrainian women aged 17-44 are used to examine the association between physical violence perpetrated by a sexual partner (defined as kicking, hitting, slapping, pushing, or attacking with a weapon) and sexual health knowledge, sexual behavior, and the likelihood of reporting a sexually transmitted infection (STI). Such violence, both past and recent, is found to be associated with increased lifetime risk of acquiring an STI. Women who have been abus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 43 publications
3
30
1
Order By: Relevance
“…There was a significant decreasing association in three Bangladesh sites, Egypt and Ukraine (Koenig et al, 2003b;Bates et al, 2004;Yount, 2005;Dude, 2007) and a decreasing trend by socioeconomic group in India, Egypt and Cambodia (Kishor and Johnson, 2004;Yount and Carrera, 2006). Severe physical violence was significantly lower in high SES households compared with low SES in Mexico though there was no significant association between moderate physical violence and SES (Rivera-Rivera et al, 2004).…”
Section: Violence and Povertymentioning
confidence: 93%
See 2 more Smart Citations
“…There was a significant decreasing association in three Bangladesh sites, Egypt and Ukraine (Koenig et al, 2003b;Bates et al, 2004;Yount, 2005;Dude, 2007) and a decreasing trend by socioeconomic group in India, Egypt and Cambodia (Kishor and Johnson, 2004;Yount and Carrera, 2006). Severe physical violence was significantly lower in high SES households compared with low SES in Mexico though there was no significant association between moderate physical violence and SES (Rivera-Rivera et al, 2004).…”
Section: Violence and Povertymentioning
confidence: 93%
“…In Turkey, women who were housewives had significantly lower physical and sexual violence compared with other women. There were no significant associations between physical violence and earning an income in Haiti (Kishor and Johnson, 2004) or the Philippines (Hindin and Adair, 2002), with years in employment either during the partnership or prior to union in Mexico (Oropesa, 1997), with the woman's monthly income in India (Rao, 1997) or being employed in the Ukraine (Dude, 2007). There was also no significant association between physical and/or sexual violence and earning an income in Zambia or Cambodia (Kishor and Johnson, 2004) or with being employed and sexual violence in Lesotho (Brown et al, 2006).…”
Section: Violence and Economic Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that among women high-risk behaviours include having sex with 'highrisk' male partners (men who are living with HIV, who inject drugs or who are nonmonogamous); having multiple sexual partners; alcohol abuse; and trading sex for money, drugs and housing or other support (1,7,9,10,11). Women's age at first sexual intercourse has also been found to be associated with STI.…”
Section: Pathways To Sti Riskmentioning
confidence: 99%
“…This finding is of public health importance because forced sex may be associated with non-use of condoms (Dude, 2007). We suggest further exploration of this phenomenon among both males and females in the intervention.…”
Section: Brief Reportmentioning
confidence: 99%